Rescue of Prothrombin-deficiency by Transgene Expression in Mice - Sun, William Y.; Coleman, Mallory J.; Witte, David P.; Degen, Sandra J. F. (Thrombosis and Haemostasis, 2002)
Prothrombin has diverse biological functions in addition to its well established role in blood coagulation. In order to study these functions in more detail mouse model systems are needed. Since deficiency of prothrombin in mice results in partial embryonic lethality and neonatal death, alternative approaches are required to study the biology of prothrombin in the adult mouse. The liver is the major site of synthesis of prothrombin and therefore liver-specific promoters were used to express prothrombin in transgenic mice. Mice generated from crosses with these transgenic mice and mice hemizygous for the knock-out allele were used to test whether liver-specific expression is sufficient to correct the phenotype of null mice and whether liver-specific expression is sufficient for the development and survival of mice to adulthood. The mouse albumin promoter/enhancer was used initially for transgene expression without success in obtaining transgene positive, endogenous prothrombin null mice. Two lines of transgene positive, endogenous prothrombin deficient mice were obtained using the mouse transthyretin (TTR) promoter/enhancer driving expression of a human prothrombin cDNA. One line was able to rescue both the embryonic and the neonatal lethality while the other line was only able to correct the embryonic lethality. Expression of prothrombin was restricted to the liver and stomach in one line and to the liver, pancreas, stomach and kidney in the other line of mice. Thrombin activity for one line was determined to be at 5-10% of wildtype levels. These mice developed normally and did not have spontaneous bleeding events unless traumatized. Therefore, transgenic expression of human prothrombin is sufficient for the rescue of the lethality found for prothrombin deficiency in mice.
Keywords: Prothrombin; thrombin; transgenic mice; transthyretin promoter